Knowledge of dentistry students on bisphosphonate-related osteonecrosis of the jaw - Maeda, Claudia Yumi (2022)
Objective: Bisphosphonates are anti-resorptive drugs used in the control and treatment of calcium and bonemetabolism disorders. Despite their high clinical efficacy, these drugs have been associated with bisphosphonaterelatedosteonecrosis of the jaw. The goal of this study is to evaluate the knowledge of final year undergraduatedentistry students on bisphosphonate-related osteonecrosis of the jaw. Material and Methods: A sample of 100students from private institutions in the state of São Paulo was invited to complete a questionnaire relating tobisphosphonates and the risk factors associated with the development of osteonecrosis of the jaws. Results: 66%of the students did not recognize any bisphosphonate (p=0.0019) and 79% did not recognize their trademarknames (p<0.0001). 60% of the students recognized osteonecrosis of the jaws as a side effect of bisphosphonates(p<0.0001) and 56% identified at least one risk factor associated with the drug that may contribute to the side effect(p<0.0001). 66% of the students stated that their course did not provide any lectures on the topic (p<0.0001).Conclusion: The knowledge of dentistry students about bisphosphonates and bisphosphonate-related osteonecrosis ofthe jaw is variable. This may be related to an inadequate discussion of this topic during their undergraduate studies.KEYWORDSBisphosphonates; Osteonecrosis; Dentistry students.